Increasing Kingella Identification in Bone and Joint Infections in Young Children. (4th October 2017) - Quick, Rachel; Williams, John; Cosgrove, Peter; Kahlden, Kyle; Fernandez, Marisol; Thoreson, Lynn; Hauger, Sarmistha
Abstract: Background: Kingella kingae is an increasingly recognized pathogen among young children with bone and joint infections. Antibiotics given to cover methicillin-resistant Staphylococcus aureus are not effective against Kingella, and necessitate additional empiric antibiotics in this age group. Improving Kingella identification can narrow antibiotic choices and improve efficacy for long-term oral therapy. Methods: We implemented a bone and joint infection guideline at a free standing children's hospital that called for early imaging, focal sampling, and polymerase chain reaction (PCR) testing for culture-negative specimens. The goal was to increase identification of Kingella and other pathogens to improve targeted antimicrobial therapy. Children 6 to ≤ 60 months of age with uncomplicated acute hematogenous osteomyelitis or septic arthritis between January 1, 2009–December 31, 2016, were included in this study. Outcomes of bacterial identification were measured. Results: Charts for 49 cases that met criteria were reviewed. Prior to the algorithm, we identified Kingella in 4% (1/25) of cases. Following routine use of updated sampling and testing techniques, including PCR testing, Kingella kingae identification increased to 29% of cases (7/24; P = 0.02) and, in fact, was the predominant pathogen identified in this age group. Conclusion: Identification of Kingella was enhanced as a result of changes to sampling and testing, including PCR testing (Figure 1). Post-implementation, Kingella was more commonly identified than Staphylococcus aureus. Widespread availability of PCR testing in the future may allow for the use of narrowed antibiotic therapy and targeted transition to oral antibiotics in young children with bone or joint infection. Disclosures: All authors: No reported disclosures.